2018
DOI: 10.1590/1806-9088201700050001
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in the Organic Phase Extracted From Charcoal for Barbecue

Abstract: -Charcoal is a widely used product for barbecue, however, its quality for said use has not been well studied. Polycyclic aromatic hydrocarbons (PAHs) are a class of carcinogenic compounds that can be present in charcoal. Thus, the objective of this study was to analyze the organic phase extracted from charcoal by organic solvents, regarding the presence of PAHs. For this, a commercial charcoal brand was acquired, collected in establishments in the city of Piracicaba, São Paulo. Complementary tests were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…The amount of volatile materials in charcoal can influence the quality of cooked food, as foods can absorb the odour of these materials, thereby rendering them undesirable. Moreover, Júnior et al (2018) have reported that, depending on the amount and type of material used, charcoal can become toxic. Similarly, Kabir et al (2010); Wu et al (2015) emphasised that dermal contact over a prolonged period can have a detrimental effect on human health, owing to the presence of particulates and hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of volatile materials in charcoal can influence the quality of cooked food, as foods can absorb the odour of these materials, thereby rendering them undesirable. Moreover, Júnior et al (2018) have reported that, depending on the amount and type of material used, charcoal can become toxic. Similarly, Kabir et al (2010); Wu et al (2015) emphasised that dermal contact over a prolonged period can have a detrimental effect on human health, owing to the presence of particulates and hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…indicou o uso de carvão vegetal no churrasco para pescado, uma vez que os resultados para HPA8 foram inferiores aos obtidos pelo carvão do tipo briquete (madeira). Segundo DiasJunior et al (2017), amostras de carvão de eucalipto não apresentaram quantidades significativas de HPAs. O efeito da grelha na churrasqueira na formação de 16 HPAs em três tipos de carne (lombo bovino, barriga de porco e coxa de frango) foi avaliado por Kim, Cho e Jang (2021) usando três tipos de carvão vegetal, branco, preto e carvão extrusado (compressão de resíduos orgânicos, como cascas de coco).…”
unclassified